Characterization of combustible liquid from thermal cracking of crude palm oil by using ZSM-5 derived from Sungai Sayong pottery waste: article / Yusuf Ahmad - Ahmad, Yusuf (2018)
Demand of fossil fuels is increasing by year as the global consumption of fossil fuels also increase. Both of the problem will lead to depletion of fossil fuels. Hence, many researchers conducting research and development to find an alternative fuels for future needs. The thermal cracking process is cracking process of large organic molecular into a smaller size. There are many studies on thermal cracking of edible and non-edible oils. Hence, thermal cracking of crude palm oil (CPO) using ZSM-5 derived from Sungai Sayong pottery waste in a combustion reactor was conducted. The combustible liquid recovered from the process were characterized using bomb calorimeter, Fourier Transform Infrared Spectroscopy (FTIR) analysis and Gas Chromatography Mass Spectrometry (GCMS) analysis. The results showed that using derived ZSM-5 as a catalyst in the cracking process, producing combustible liquid with an average value of calorific which is 9144 kcal/kg. During the elemental analysis, there are presence of Carbon and hydrogen. From the GCMS analysis, the highest compound that been identified is estragole followed by hexadecanoic acid methyl ester. These are proven as during the FTIR analysis, there is three type of functional group which alkyl, carboxylic acid and alcohol-phenol group. The derived ZSM-5 is not suitable to the all type of oil as referring to the performance in stearin cracking process.